HUBUNGAN OBESITAS DENGAN DIABETES MELITUS TIPE DI WILAYAH KERJA PUSKESMAS KEBUN SIKOLOS KOTA PADANG PANJANG TAHUN 2021 - Nur’afifah, Fauziah; Burhan, Ida Rahmah; Sulastri, Delmi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Type 2 diabetes mellitus is a metabolic disease characterized by increased blood glucose levels or hyperglycemia caused by insulin resistance. One of the biggest risk factors for type 2 diabetes mellitus is obesity. Excessive fat accumulation in obesity results in an inflammatory process that results in damage to insulin as a regulator of sugar in the blood. The purpose of this study was to determine the relationship between obesity and type 2 diabetes mellitus in the working area of Kebun Sikolos Health Center, Padang Panjang City in 2021. This research is an observational analytic study with a case control research design that examines the relationship between obesity and type 2 diabetes mellitus in the working area of Kebun Sikolos Health Center, Padang Panjang City in 2021. The sample of this study was 78 people consisting of 39 patients with type 2 diabetes mellitus as the case group and 39 patients who did not suffer from diabetes mellitus as the control group were obtained using a simple random sampling technique. Data collection in this study used medical record data. Data analysis used the Chi-Square test. The results of this test obtained a significance value (p-value) of 0.007 (p <0.05). The p-value is less than 0.05 (0.007 <0.05) so the test decision is H0 is rejected, which means there is a relationship between obesity and type 2 diabetes mellitus in the working area of Kebun Sikolos Health Center, Padang Panjang City in 2021. The conclusion obtained is that there is a relationship between the two variables, namely obesity and type 2 diabetes mellitus. The incidence of obesity is more common in people with type 2 diabetes mellitus compared to those who do not suffer from diabetes mellitus